1995
DOI: 10.1029/95jb01967
|View full text |Cite
|
Sign up to set email alerts
|

Open‐system melting in the upper mantle: Constraints from the Hayachine‐Miyamori ophiolite, northeastern Japan

Abstract: The Hayachine and Miyamori hydrous ultramafic complexes, northeastern Japan, exhibit not only diverse lithological variations from very primordial spinel lherzolites (olivine forsterite mol % = 89 (Fo89), spinel 100Cr/(Cr+Al) (Cr #) =10) to refractory harzburgites (Fo93, spinel Cr #=70) but also show diverse trace element characteristics in amphiboles and clinopyroxenes correlated with the major element behavior. Some of the most primitive lherzolites are from the Hayachine complex and contain a clinopyroxene … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
104
0
1

Year Published

2000
2000
2016
2016

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 122 publications
(108 citation statements)
references
References 42 publications
3
104
0
1
Order By: Relevance
“…It has not yet been specified whether the matter added is solid or liquid; Ozawa & Shimizu (1995) referred to fluid. The choice is significant, and at least three options are open.…”
Section: Theorymentioning
confidence: 99%
See 2 more Smart Citations
“…It has not yet been specified whether the matter added is solid or liquid; Ozawa & Shimizu (1995) referred to fluid. The choice is significant, and at least three options are open.…”
Section: Theorymentioning
confidence: 99%
“…Sobolev & Shimizu (1993) applied continuous melting theory to the origin of "super-depleted" (SL) melt (glass) trapped in mantle materials. Ozawa & Shimizu (1995) invoked an opensystem continuous melting regime to explain features of the Hayachine and Miyamori ultramafic complexes of Japan. Albarède (1995) discussed the formalism of continuous melting, but without considering the nonmodal theory.…”
Section: Fluid Dynamics and Fractionationmentioning
confidence: 99%
See 1 more Smart Citation
“…Among the first the estimates of D (apatite / melt) values were obtained by the example of samples from the natural system -basanites [106], and later on -based on the results of experimental studies of basaltic melts [109]. These observations showed that all the REE have values of D (apatite / melt) > 1.…”
Section: Apatitesmentioning
confidence: 99%
“…The small letter n denotes the chondrite normalized value. Arrows are melt extraction trends estimated from abyssal peridotite (Johnson et al, 1990;Hellebrand et al, 2001 (Johnson et al, 1990;Ozawa and Shimizu, 1995;Xu et al, 2000) HREE REE pattern Ti, Zr HFSE (Vasseli et al, 1997), (c) for the peridotite xenoliths from Eifel, Germany (Witt Eickschen et al, 1993), (d) for the peridotite xenoliths from South Patagonia (Gorring and Kay, 2000), (e) for the peridotite xenoliths from Samoa islands (Hauri and Hauri, 1994).…”
Section: ( ) In Situmentioning
confidence: 99%